Pengaruh Dukungan Sosial dan Kemampuan Karyawan Terhadap Kinerja Karyawan ( studi empiris pada PT.BRIS POEY TRANS ) - Fahmi Abdul Muiz; Faizal Mulia Z; Erry Sunarya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the effect of social support and employee skills on employee performance caused by the lack of support and missed communication between employees at PT. BRIS POEY TRANS. Based on the results of the study, the relationship between social support and employee performance was 4.209 and a significant value of 0.000 showed that there was a positive and significant effect, in addition to the Employee Ability of 3.953 and a significant value of 0.000, there was a positive and significant effect because t > 0. Contribution in measuring the effect of social support and the ability of employees to employee performance of 0.551 or 55.1%. So it can be seen that the influence of social support and employee ability has a strong influence and the biggest influence on employee performance is the social support variable. Based on the results of the study showed a positive and significant influence between social support and employee performance and showed a positive and significant influence between employee abilities on employee performance. The influence is marked by the high ability possessed by employees such as the magnitude of the sense of responsibility and loyalty of the employees of PT. Bris Poey Trans. Keywords: Social Support, Employee Ability, Employee Performance